Two species of Lumbricillus (Enchytraeidae, Annelida) new to Antarctica - Lee, Jeounghee; Klinth, Mårten J; Jung, Jongwoo (Polar Research, 2019)
The intertidal fauna of the Antarctic Peninsula has a relatively high species diversity, due to its warmer environment compared to other parts of Antarctica. Marine oligochaetes are, in general, one of the most diverse and ecologically important benthic organism groups, at least in the littoral zone. Antarctica has been one of the least studied areas with regard to oligochaete diversity. Here we report two Lumbricillus species (Lumbricillus antarcticus Stephenson, 1932 and Lumbricillus sejongensis sp. nov.) new to Antarctica, found in a tidal pool on the Barton Peninsula, King George Island. The diversity of this genus remains poorly known for Antarctica and the Subantarctic islands, and what we know is based on a few patchy studies.
Keywords: Sørishavet; belteormer; bentiske organismer; biodiversitet; fauna; marin biologi; tidevann

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann